2009
DOI: 10.1007/s00542-009-0834-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of hybrid differential transformation/finite difference method to nonlinear analysis of micro fixed-fixed beam

Abstract: Analyzing the dynamic response of electrostatic devices is problematic due to the complexity of the interactions between the electrostatic coupling effect, the fringing field effect and the nonlinear electrostatic force. To resolve this problem, this study presents an efficient computational scheme in which the nonlinear governing equation of the electrostatic device is obtained in accordance with Hamilton's principle and is then solved using a hybrid differential transformation/finite difference method. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…An infinitesimal transformation is applied as an operator on itself and, both functions ξ and η defined in (9), must satisfy the following equality [11]: η xx + (2η xy − ξ xx )ý +(η yy − 2ξ xy )ý2 − ξ yy ý3 + (η y − 2ξ x − 3ξ y ý)ω = ω x + ηω y + ((η x − ξ x )ý− ξ y ý2) ω ý (12) Subsequently, ξ and η can be calculated by decomposed [3][4][5][6] into a system of partial differential equations. The following Lie symmetries which including rotation, translation and scaling was considered to calculate ξ and η. ξ = C 1 + C 2 x + C 3 y η = C 4 + C 5 x + C 6 y (13)…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…An infinitesimal transformation is applied as an operator on itself and, both functions ξ and η defined in (9), must satisfy the following equality [11]: η xx + (2η xy − ξ xx )ý +(η yy − 2ξ xy )ý2 − ξ yy ý3 + (η y − 2ξ x − 3ξ y ý)ω = ω x + ηω y + ((η x − ξ x )ý− ξ y ý2) ω ý (12) Subsequently, ξ and η can be calculated by decomposed [3][4][5][6] into a system of partial differential equations. The following Lie symmetries which including rotation, translation and scaling was considered to calculate ξ and η. ξ = C 1 + C 2 x + C 3 y η = C 4 + C 5 x + C 6 y (13)…”
Section: Theorymentioning
confidence: 99%
“…There are several methods to obtain the governing differential equation. The common methods are using either Hamiltonian [2] or energy [3] methods. Many researchers used several different approaches to linearize and simplify the governing equations given their high non-linearity.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the first-order fringing field correction of the electrostatic force per unit length of the beam is [25] F elec = ε 0 wV 2 2(g − z) 2 …”
Section: Article In Pressmentioning
confidence: 99%
“…Kuo [12] applied differential transformation theory to investigate the velocity and temperature distributions associated with a free convection boundary-layer flow over a vertical plate. Chen et al [21] demonstrated that the hybrid differential transformation and finite difference method provide a precise and computationallyefficient means of analyzing the nonlinear dynamic behavior of fixedfixed micro-beams. The same group also used the hybrid method to analyze the nonlinear dynamic response of an electrostaticallyactuated micro circular plate subject to the effects of residual stress and a uniform hydrostatic pressure acting on the upper surface [22].…”
Section: Introductionmentioning
confidence: 99%